TANTANGAN DAN PELUANG PENGEMBANGAN SISTEM INFORMASI DI INDUSTRI KREATIF: PERSPEKTIF TEKNOLOGI DAN INOVASI - Syawalia Arifa; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In this article, a technology and innovation perspective is used to see how creative industries develop information systems. Limited infrastructure and limited resources to the threat of rapid digitalization are some of the problems that burden the modern creative industry. However, there are great opportunities to increase productivity, efficiency and quality of creative products thanks to technological advances and innovation. In addition, creative industry players can more easily collaborate and connect with markets around the world thanks to advances in the internet and contemporary technology. Although digitalization brings challenges such as tougher competition and cyber security threats, it also opens up larger markets through digital platforms such as social media and e-commerce. Ultimately, this article states that cooperation between government, the private sector and local communities is essential to maximize the potential of creative industries as the main driver of regional development.